Examining teaching and learning through feedback in open distance and e-learning: The views of the students - Lumadi, R. I. (South African Journal of Higher Education, 2023)
If virtual assessment lies at the heart of the open, distance and e-learning experience, then information about student responses to the assessment is vital. Feedback is generally thought of as being conveyed by the e-tutor to the student; however, the feedback mechanisms ecosystem demonstrates that student-to-lecturer and student-to-institution are also vital types of feedback. The study followed the mixed method approach to investigate the perceptions of 148 students in the Department of Educational Management universities in South Africa. Of the participants, 143 responded to questionnaires, and the remaining 5 were interviewed by means of a semi-structured interview schedule. The findings indicate that e-tutors did provide feedback to their students, and also that the efficient provision of effective feedback is essential to student learning and continues to be a key concern for many higher education institutions. However, the study also revealed that e-tutors provided conventional, one-dimensional assessment feedback, with negative consequences for teaching and learning. It is recommended that e-tutors should give feedback that encourages students rather than expressing criticism.